Papéis ocupacionais desempenhados por mães de crianças com transtorno do espectro autista - Barros, Larissa Fabiane de Sousa (Universidade Federal de São Carlos, 2025)
Autism Spectrum Disorder (ASD) is characterized by persistent deficits in communication and social interaction, as well as restrictive and repetitive patterns of behavior, varying across three levels of support needs. The child’s level of dependence may lead to significant changes in the routine of the primary caregiver, usually the mother. These responsibilities, combined with the constant care required by the child, may result in changes or even the disruption of her daily activities and occupational roles. Occupational roles are determined according to each individual’s duties and choices and are organized in a way that contributes to the construction of personal and social identity. This study aims to understand the occupational roles performed by mothers of children with Autism Spectrum Disorder (ASD) and the occupational impacts resulting from the arrival of and living with a child with this diagnosis. This is a qualitative, descriptive, multiple-case study involving five mothers of children with ASD who were receiving occupational therapy follow-up at a clinic in the interior of the state of São Paulo. Data were collected using the Occupational Roles Checklist (ORC) and a semi-structured interview guide. The analysis of the interview results was conducted through descriptive case synthesis and simple statistics. It was found that, among the 10 occupational roles assessed, 8 were impaired or interrupted. The occupational role related to domestic services was maintained, and the caregiver role increased after the arrival of the child with ASD. The worker role, performed in the past by all five participating mothers, continued to be exercised in the present by only two of them. On the other hand, the caregiver role, previously performed by three of the five mothers, came to be assumed by all of them in the present. Both roles were reported as having great importance by the participants. Occupational changes require adaptations within these mothers’ life contexts, demanding a reorganization of daily activities to meet the child’s care needs. These findings provide an understanding of the roles performed by mothers of children with ASD, as their routines and occupations undergo significant modifications. Such changes require constant adaptations in their roles and occupations, compelling them to reorganize their daily activities to meet the specific demands of their children. The study made it possible to understand the roles performed by the interviewed mothers, as well as their altered occupations. Furthermore, it highlighted the volitional values related to occupational roles that were discontinued due to the care of a child with ASD.
Papéis ocupacionais desempenhados por mães de crianças com transtorno do espectro autista
Keywords: Mães; Ocupação; Transtorno do Espectro Autista; Terapia Ocupacional; Mothers; Occupation; Autism Spectrum Disorder; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar